2017
DOI: 10.1038/ctg.2016.68
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic vs. Surgical Interventions for Painful Chronic Pancreatitis: What is Needed for Future Clinical Trials

Abstract: The treatment of painful chronic pancreatitis remains controversial. The available evidence from two randomized controlled trials favor surgical intervention, whereas an endotherapy-first approach is widely practiced. Chronic pancreatitis is complex disease with different genetic and environmental factors, different pain mechanisms and different treatment modalities including medical, endoscopic, and surgical. The widely practiced step-up approach remains unproven. In designing future clinical trials there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It is worth noting that the effect size of sham treatment in these studies is of a similar magnitude to that seen in studies investigating endoscopic and surgical treatment for painful CP (table 1). Unfortunately, the ethical challenges of conducting sham-controlled studies in surgery (open or laparoscopic) in CP are well recognised,59 but in contrast, it is possible to conduct sham-controlled endoscopic treatments 3…”
Section: The Cons Of Interventional Treatment Of Pain In Chronic Pancmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the effect size of sham treatment in these studies is of a similar magnitude to that seen in studies investigating endoscopic and surgical treatment for painful CP (table 1). Unfortunately, the ethical challenges of conducting sham-controlled studies in surgery (open or laparoscopic) in CP are well recognised,59 but in contrast, it is possible to conduct sham-controlled endoscopic treatments 3…”
Section: The Cons Of Interventional Treatment Of Pain In Chronic Pancmentioning
confidence: 99%
“…While there are many clinical studies that support invasive treatments, there is a paucity of high-quality randomised controlled trials (RCTs). As a result, the current guidelines for endoscopic and surgical treatments for painful CP are inconsistent and tend to reflect a specialty bias 3. For example, the German guidelines4 recommend surgery as the most effective treatment of pain, whereas the European Society of Gastrointestinal Endoscopy5 and the international evidence-based (HaPanEU) guidelines1 advice a ‘step-up approach’ incorporating both conservative, endoscopic and surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that surgery (specifically pancreatic drainage and/or resection) represents a safe, effective, and durable intervention in patients with chronic pancreatitis that provides better long-term symptom relief than endoscopic interventions. 12,13,[17][18][19] This is reflected by our data, which demonstrates a nearly 50% long-term symptom relief rate even among patients who have failed endoscopic management. However, despite its safety, the risks of a surgical procedure exceed that of endoscopic interventions.…”
Section: Discussionmentioning
confidence: 63%
“…ERCP with stenting of the pancreatic duct increases drainage of the gland, which, for early stage disease, effectively decreases abdominal pain. [12][13][14][15] For more advanced disease, robust data for the immediate and long-term role of endoscopic stenting is lacking. 12,16 The subset of patients in whom endoscopic interventions provide adequate pain relief over the course of their disease remains unclear, though our findings suggest it may be limited to those patients meeting fewer EUS criteria for chronic pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation